Frog Reproductive Modes in Central Sarawak (Kapit Division), Malaysian Borneo - Adi Shabrani, Bin Mohammad Ridzuan (unimas, 2016)
Amphibians are particularly sensitive to environmental change, and many studies have demonstrated the effect of anthropogenic disturbance on populations. Several ecological traits within amphibians are vulnerable to landscape change, including reproductive strategies. Borneo is one of the richest tropical regions for amphibians, yet remains poorly understood in many aspects of their diversity and ecology. Rapid deforestation occurring on Borneo poses major threats to amphibians via habitat degradation and isolation. Anuran amphibians (frogs) are grouped within different guilds, defined as groups whose members exploit similar breeding sites. This study investigates how guilds of frogs respond to different degrees of disturbance, using proportionate canopy cover as a surrogate for disturbance and reproductive modes for guilds, within a lowland dipterocarp forest in central Sarawak. Additionally, variation in body and clutch size within different amphibian guilds was also investigated. Visual and Acoustic Encounter Surveys along transects were conducted at four sites between May 2014 to April 2015. A total of 46 species, associated with 12 reproductive modes, were recorded, in addition to two unassigned to a specific mode.